DATAMESOP: DATAset on Stable Isotope Measurement (Strontium, Oxygen and Carbon) of Archaeological and Non-Archaeological Materials from South-West Asia for MESOPotamia - Matteo Giaccari; Licia Romano; Franco D’Agostino; Mary Anne Tafuri (Journal of Open Archaeology Data, 2025)
DATAMESOP is one of the first comprehensive isotopic datasets aimed at supporting bioarchaeological studies in ancient Mesopotamia. The dataset compiles radiogenic strontium and stable carbon, and oxygen isotope measurements from both archaeological (human and animal remains and plant and soil samples) and nonarchaeological sources (surface rocks, soil, dust, water, and rainwater) in South-West Asia. The data have been collected, ensuring the quality and reliability of isotopic measurements and the comparability of the standards, from published studies. This dataset is designed to be user-friendly for archaeologists and isotope specialists, including contextual information that might facilitate data use and interpretation, particularly in regions like Mesopotamia (Iraq, Iran, and Turkey), where isotopic data are scarce and, more generally, challenging to obtain. We believe that this comprehensive dataset will contribute to isotopic investigations in these regions. The dataset is stored in the Pandora platform.